EKSTERNALISASI GAYA PAKAIAN THE NURULS GENERASI Z DALAM BERPAKAIAN ISLAMI DI KABUPATEN BOGOR - Sarah, Nayla; Ernawati, Erna; Surizkika, Aldi (Fakultas Ilmu Dakwah dan Komunikasi, 2025)
The majority of various groups, including generation Z, choose a simple style of clothing as their daily clothing style with a percentage of 73%. On the other hand, Islamic clothing is often juxtaposed with the idea of ​​